Localization of the Vertical Part of the Facial Nerve in the High-Resolution Computed Tomography During Pediatric Cochlear Implantation - Mahmoud Mandour; Mohamed Amer; Saad Elzayat; Edoardo Covelli; Maurizio Barbara; Rasha Lotfy; Haitham H. Elfarargy; Mohamed Osama Tomoum (Journal of International Advanced Otology)
BACKGROUND: This study proposed a classification of the vertical portion of the facial nerve (VPFN) location, incorporating the previous classifications regarding the posterior-to-anterior and medial-to-lateral dimensions. We also evaluated the implication of this proposed classification on the round window visibility during pediatric cochlear implantation (CI).